2008
DOI: 10.1007/s00531-008-0348-6
|View full text |Cite
|
Sign up to set email alerts
|

Using ocean quahog (Arctica islandica) shells to reconstruct palaeoenvironment in Öresund, Kattegat and Skagerrak, Sweden

Abstract: Shells of Arctica islandica collected between 1884 and 2004 from Ö resund, Kattegat and Skagerrak (Swedish West Coast) were used to monitor local climate variations and the influence of human activities on the local environment. For this purpose, we analysed the growth, structure and chemical composition of these shells and compared them with shells collected from Kiel Bay, Norway and Iceland. The growth rate of the studied shells registers an NAO periodicity of ca 8 years. However, the observed signal is weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 13 publications
5
47
0
Order By: Relevance
“…Currently, the source of the intrinsic fluorescence of A. islandica shells is unknown; A. islandica is known to precipitate its aragonite shell within an organic polymer matrix, which likely includes chitin polysaccharides and proteins (e.g., Addadi et al 2006;Cusack and Freer 2008;Dunca et al 2009). Perez-Huerta et al (2008) suggested that organic macromolecules associated with chitin polysaccharides and proteins in calcitic brachiopods (Terebratalia transversa and Novocrania anomala) are the likely cause of shell fluorescence in these species.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the source of the intrinsic fluorescence of A. islandica shells is unknown; A. islandica is known to precipitate its aragonite shell within an organic polymer matrix, which likely includes chitin polysaccharides and proteins (e.g., Addadi et al 2006;Cusack and Freer 2008;Dunca et al 2009). Perez-Huerta et al (2008) suggested that organic macromolecules associated with chitin polysaccharides and proteins in calcitic brachiopods (Terebratalia transversa and Novocrania anomala) are the likely cause of shell fluorescence in these species.…”
Section: Discussionmentioning
confidence: 99%
“…The organization lacks of specific structural arrangement typical of other types of microstructures such as the crossed-lamellar and crossed-acicular microstructures. The latter are the main component characterizing the iOSL and ISL (Dunca et al, 2009). Here, elongated units are arranged with two main dip directions, resulting in a relative oblique alignment.…”
Section: A Islandica Shell Organizationmentioning
confidence: 99%
“…First, we applied the Morlet wavelets (Morlet 1983; Torrence and Compo 1998), a continuous wavelet transform, proven and tested in climate time series analysis (Lau and Weng 1995;Dunca et al 2009;Schöne and Fiebig 2009;Wanamaker et al 2009). The transform was based on the method described in Torrence and Compo (1998) by means of Wavelet software provided by these authors.…”
Section: Statistical Evaluationmentioning
confidence: 99%